Penyelenggaraan Jalur Pendidikan Formal dan Nonformal: Studi Kasus di PAUD Terpadu Salsabila Al-Muthi'in Yogyakarta - Nurul Maziyatul Hasanah (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2019)
The implementation of formal and non-formal education channels aims to find out how the service components are in Early Childhood Education. This type of research is qualitative research. The subject used in this study was the principal of Early Childhood Education Salsabila Al-Muthi’in Yogyakarta. Data collection techniques using observation, interviews, and documentation. Data analysis used the Miles and Huberman model which included data presentation, data reduction, and drawing conclusions. The results showed that Salsabila Al-Muthi'in Integrated Early Childhood Education Yogyakarta, there are 7 components of Early Childhood Education implementation in providing formal and non-formal Early Childhood Education, among the seven components including: curriculum, students, educators and education staff, facilities and infrastructure, management, financing and partnership.a